Addressing the "risk environment" for injection drug users: the mysterious case of the missing cop. - Burris, Scott; Blankenship, Kim M; Donoghoe, Martin; Sherman, Susan; Vernick, Jon S; Case, Patricia; Lazzarini, Zita; Koester, Stephen (The Milbank quarterly, 2004)
Ecological models of the determinants of health and the consequent importance of structural interventions have been widely accepted, but using these models in research and practice has been challenging. Examining the role of criminal law enforcement in the "risk environment" of injection drug users (IDUs) provides an opportunity to apply structural thinking to the health problems associated with drug use. This article reviews international evidence that laws and law enforcement practices influence IDU risk. It argues that more research is needed at four levels--laws; management of law enforcement agencies; knowledge, attitudes, beliefs, and practices of frontline officers; and attitudes and experiences of IDUs--and that such research can be the basis of interventions within law enforcement to enhance IDU health.
Keywords: Communicable Diseases; Criminal Law; Health Policy; HIV Infections; Humans; Public Health; Risk Factors; Substance Abuse, Intravenous; United States